Tinjauan Pelaksanaan Transfer Melalui BRI Mobile - Nadiyah Syakirah (2021)
The rapid progress and development of information technology has affected the banking industry, just as Internet Banking is one manifestation of this technological development. BRI as one of the state-owned banks in Indonesia has been using the money transfer/transfer service facility with the Internet Banking application since 2012. The author feels that it is very appropriate for the current phenomenon, namely the outbreak of the Covid-19 pandemic. Because we do more activities at home and minimize activities outside the home, one of which is banking transactions, namely transfers. In today's conditions, there are definitely more customers who use Internet Banking than coming to an ATM for transfers because it can save time and without having to leave the house. So, in this final project report, the author discusses the Overview of the Implementation of Transfers Through BRI Mobile. The purpose of this Final Project Report is to obtain complete information and data on the Implementation of Transfers Through BRI Mobile. The sources of discussion of the Final Project Report used are books, journals, websites and questionnaires. The results of the Final Project Report obtained are the implementation of transfers through BRI Mobile from the conditions that must be met by the user to how to use the transfer feature on BRI Mobile.